KNOWLEDGE ABSORPTIVE CAPACITY AND PROCESS INNOVATION: THE MODERATING EFFECT OF ENVIRONMENTAL DYNAMISM - Ramayah, T.; Kheng, Khoo Kah; Yeap, Jasmine A.L. (Journal of Technology Management and Business, 2014)
A firm’s absorptive capacity through its knowledge-processing capabilities is crucial in increasing the firm’s innovation performance and fostering competitive advantage. The purpose of this study, therefore, was to investigate the relationship between firms’ absorptive capacity and their process innovation performance by taking into consideration absorptive capacity as a multidimensional, dynamic construct consisting of knowledge acquisition, dissemination and utilization capabilities. Furthermore, this study examined the moderating effect of environmental dynamism on the relationship between firms’ absorptive capacity and innovation performance. Data was gathered from 69 manufacturing firms operating in the northern region of Malaysia. The analyses results showed that knowledge dissemination and utilization had a significant, positive relationship with process innovation. It was also found that in highly dynamic environmental conditions, the impact of knowledge acquisition on process innovation is less pronounced. In stark contrast, the impact of knowledge dissemination on process innovation is enhanced during highly dynamic environmental conditions.